Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12968-016-0306-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of self-gated radial cardiovascular magnetic resonance to detect and classify arrhythmias (atrial fibrillation and premature ventricular contraction)

Abstract: BackgroundArrhythmia can significantly alter the image quality of cardiovascular magnetic resonance (CMR); automatic detection and sorting of the most frequent types of arrhythmias during the CMR acquisition could potentially improve image quality. New CMR techniques, such as non-Cartesian CMR, can allow self-gating: from cardiac motion-related signal changes, we can detect cardiac cycles without an electrocardiogram. We can further use this data to obtain a surrogate for RR intervals (valley intervals: VV). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…We therefore utilized a MRI sequence to perform in-scanner measurement of heart rate during each session. The sequence acquired the center k-space repeatedly at an interval of 8.0 ms, thereby yielding a time course of MR signal intensity, the period of which is the R-R interval (49). Two measurements were performed in each session and the values were averaged.…”
Section: Heart Rate Measurementmentioning
confidence: 99%
“…We therefore utilized a MRI sequence to perform in-scanner measurement of heart rate during each session. The sequence acquired the center k-space repeatedly at an interval of 8.0 ms, thereby yielding a time course of MR signal intensity, the period of which is the R-R interval (49). Two measurements were performed in each session and the values were averaged.…”
Section: Heart Rate Measurementmentioning
confidence: 99%
“…This approach does not rely on assumptions about motion models (e.g., translation, affine, or nonrigid) as in registration‐based correction methods, maintains high scan efficiency, and provides access to additional physiologic information of potential clinical value . Successful applications of XD‐GRASP have been demonstrated for free‐breathing liver MRI , whole‐heart coronary MRA and cardiac cine MRI .…”
Section: Introductionmentioning
confidence: 99%
“…Piekarski et al previously reported a similar measure of self-gating signal that could separate non-arrhythmic patients from arrhythmic patients. 37 While Piekarski does not report an AF burden threshold for low versus high AF burden, their results suggest a threshold of just under 17.0%, a value that is close to the AF burden of the least arrhythmic patient with persistent AF (Table 1, subject 19). We investigated splitting patients into groups of persistent/permanent AF versus paroxysmal AF (PAF), and found it preserved the hemodynamic relationships seen between low and high AF burden.…”
Section: Discussionmentioning
confidence: 92%